Phytogeography and speciation in the vegetation of the eastern Cape - G. E. Gibbs Russell; E. R. Robinson (Bothalia: African Biodiversity & Conservation, 1981)
The eastern Cape is a region of variable environmental factors, with a flora estimated at about 3 600 -4 000 species and encompassing 21 of Acocks’s (1975) veld types. It lies at the edges of the major phytochoria present in southern Africa, with many tropical species reaching the southern and western limits o f their distribution, and many south-western Cape and Karoo species reaching the northern and eastern limits of their distribution. The apparently low incidence o f species endemic to the eastern Cape may be the result of selection for ‘generalist’ genotypes and the close proximity of different phytochoria, which may allow species to migrate between phytochoria to fill niches resulting from environmental change.